1999
DOI: 10.1038/7243
|View full text |Cite
|
Sign up to set email alerts
|

G-protein-coupled receptors act via protein kinase C and Src to regulate NMDA receptors

Abstract: The N-methyl-D-aspartate (NMDA) receptor contributes to synaptic plasticity in the central nervous system and is both serine-threonine and tyrosine phosphorylated. In CA1 pyramidal neurons of the hippocampus, activators of protein kinase C (PKC) as well as the G-protein-coupled receptor ligands muscarine and lysophosphatidic acid enhanced NMDA-evoked currents. Unexpectedly, this effect was blocked by inhibitors of tyrosine kinases, including a Src required sequence and an antibody selective for Src itself. In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

16
305
2
2

Year Published

2001
2001
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 351 publications
(325 citation statements)
references
References 35 publications
16
305
2
2
Order By: Relevance
“…Src-family kinases can phosphorylate NR2B subunits at tyrosine residue 1472, which is critical for NR2B subunit-containing NMDAR surface expression and functional potentiation (Ali and Salter, 2001;Groveman et al, 2012;Lu et al, 1999a;Salter, 1998;Salter and Kalia, 2004;Sinai et al, 2010;Stramiello and Wagner, 2008). The present study revealed that NR2B phosphorylation at Y1472 in the DH increased following testing in the cocaine-paired context, relative to home cage exposure.…”
Section: Discussionmentioning
confidence: 49%
See 1 more Smart Citation
“…Src-family kinases can phosphorylate NR2B subunits at tyrosine residue 1472, which is critical for NR2B subunit-containing NMDAR surface expression and functional potentiation (Ali and Salter, 2001;Groveman et al, 2012;Lu et al, 1999a;Salter, 1998;Salter and Kalia, 2004;Sinai et al, 2010;Stramiello and Wagner, 2008). The present study revealed that NR2B phosphorylation at Y1472 in the DH increased following testing in the cocaine-paired context, relative to home cage exposure.…”
Section: Discussionmentioning
confidence: 49%
“…Five members of the family have been identified in the mammalian brain, including Src, Fyn, Lyn, Yes, and Lck (Salter and Kalia, 2004). In cultured hippocampal neurons or brain slices, activation of Src-family kinases increases the phosphorylation of NR2B NMDAR subunits (Lu et al, 1999a;Stramiello and Wagner, 2008), which is required for NR2B subunit surface expression and NMDAR function (Ali and Salter, 2001;Groveman et al, 2012;Lu et al, 1999a;Salter and Kalia, 2004;Stramiello and Wagner, 2008). Conversely, pharmacological inhibition of Src-family kinases in the dorsomedial striatum decreases the phosphorylation of NR2B subunits and the expression of drugprimed alcohol-seeking behavior (Wang et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…SFKs can be modulated by tyrosine phosphatases, G-protein-coupled receptors, receptor protein tyrosine kinase signaling, the Ras pathway, and the cytokine receptor and integrin pathways. Many of the physiological actions of NMDA receptors are critically dependent upon SFKs (Gingrich et al, 2004;Hayashi and Huganir, 2004;Kalia and Salter, 2003;Lu et al, 1999). As an example, SFKs are necessary for the induction of long-term potentiation in the CA1 region of hippocampus (Salter and Kalia, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Several lines of evidence support a role for PKC in potentiating NMDA receptor function (39,40). PKC phosphorylates GluN2B subunit on serine residues (Ser 1303 or Ser 1323 ) located in its carboxylterminal domain (41), and each of these phosphorylations induces a potentiation of NMDA currents (41,42).…”
Section: Resultsmentioning
confidence: 99%